On Interpolative Prešić-Type Set-Valued Contractions - Monairah Alansari; Ghada Ali Basendwah; Muhammad Usman Ali (Journal of Mathematics)
This study aims to present the notions of interpolative Prešić-type set-valued contractions for the set-valued operators defined on product spaces. With the help of these notions, we have studied the existence of fixed points for such set-valued operators. An application of the obtained results is also discussed with the help of graph theory.